Fursultiamine Alleviates Choroidal Neovascularization by Suppressing Inflammation and Metabolic Reprogramming - Do, Ji Yeon (Invest Ophthalmol Vis Sci, 2020)
PURPOSE: To assess the therapeutic effects of fursultiamine on choroidal neovascularization (CNV) through its modulation of inflammation and metabolic reprogramming in the retinal pigment epithelium (RPE). METHODS: The anti-angiogenic effects of fursultiamine were assessed by measuring vascular leakage and CNV lesion size in the laser-induced CNV mouse model. Inflammatory responses were evaluated by quantitative polymerase chain reaction, western blot, and ELISA in both CNV eye tissues and in vitro cell cultures using ARPE-19 cells or primary human RPE (hRPE) cells under lipopolysaccharide (LPS) treatment or hypoxia. Mitochondrial respiration was assessed by measuring oxygen consumption in ARPE-19 cells treated with LPS with or without fursultiamine, and lactate production was measured in ARPE-19 cells subjected to hypoxia with or without fursultiamine. RESULTS: In laser-induced CNV, fursultiamine significantly decreased vascular leakage and lesion size, as well as the numbers of both choroidal and retinal inflammatory cytokines, including IL-1β, IL-6, IL-8, and TNF-α. In LPS-treated ARPE-19 cells, fursultiamine decreased proinflammatory cytokine secretion and nuclear factor kappa B phosphorylation. Furthermore, fursultiamine suppressed LPS-induced upregulation of IL-6, IL-8, and monocyte chemoattractant protein-1 in a dose-dependent and time-dependent manner in primary hRPE cells. Interestingly, fursultiamine significantly enhanced mitochondrial respiration in the LPS-treated ARPE-19 cells. Additionally, fursultiamine attenuated hypoxia-induced aberrations, including lactate production and inhibitory phosphorylation of pyruvate dehydrogenase. Furthermore, fursultiamine attenuated hypoxia-induced VEGF secretion and mitochondrial fission in primary hRPE cells that were replicated in ARPE-19 cells. CONCLUSIONS: Our findings show that fursultiamine is a viable putative therapeutic for neovascular age-related macular degeneration by modulating the inflammatory response and metabolic reprogramming by enhancing mitochondrial respiration in the RPE.